Comparative evaluation of topical 10% potassium hydroxide and 30% trichloroacetic acid in the treatment of plane warts - Sandhaya Jayaprasad; Radhakrishnan Subramaniyan; Shalini Devgan (Wolters Kluwer Medknow Publications, 2016)
Background: Warts are benign proliferations of skin and mucosa caused by the human papillomavirus (HPV). Plane warts are caused by HPV types 3, 10, 28, and 41, occurring mostly in children and young adults. Among the treatment modalities, topical application of trichloroacetic acid (TCA) is age old. Potassium hydroxide (KOH) has a keratolytic effect on virus-infected cells. It is less irritating, less painful, less scar forming, and can be safely used in children too. Hence, it could be a better topical agent in the treatment of plane warts. Aims and Objectives: To compare the safety and efficacy of topical 10% KOH with 30% TCA in the treatment of plane warts. Materials and Methods: Sixty consecutive patients with plane warts were randomly assigned into two arms of thirty patients each; arm A received topical 10% KOH and arm B received topical 30% TCA as a once weekly application until the complete clearance of warts or a maximum period of 12 weeks. Results: Statistically no significant difference (P = 0.07) was found between the objective therapeutic response to 10% KOH and 30% TCA at the end of study (12 weeks). However, subjective response to 10% KOH was better and statistically significant (P = 0.03). There was no recurrence of warts seen on follow-up for 3 months of complete responders in both the arms. Conclusion: 10% KOH is found to be equally effective in the treatment of plane warts compared to 30% TCA with the advantage of faster onset of action and tendency of completely clearing warts with fewer side effects.